Taxes and Caps as Climate Policy Instruments with Domestic and Imported Fuels - Strand, Jon (World Bank, Washington, DC, 2014)
This paper develops a global model of climate policy, focusing on the choice between tax and cap-and-trade solutions. The analysis assumes that the world can be split into two regions, with two fuels that both lead to carbon emissions. Region A consumes all fuels, and is responsible for defining and implementing climate policy. Region B produces all of fuel 1 (oil), while fuel 2 (interpreted as coal, natural gas, or renewables) is both produced and consumed in region A. The paper studies three model variants. All involve full policy coordination in each country block, but no coordination across blocks; and all involve an optimal producer tax on fuel 1 by region B. In model 1, region A sets two fuel consumption taxes, one for each fuel. The optimal region A tax on fuel 1 then exceeds the Pigou level as defined by the region; the tax set on fuel 2 is Pigouvian. The presence of a second fuel in region A reduces region B s optimal tax on fuel 1. In model 2, region A sets a common carbon tax, which is lower (higher) for fuel 1 (2) than in model 1. In model 3, region A sets a carbon emissions cap. This enhances region B s strategic position via the trade-off between fuels 1 and 2 in region A, following from the cap. In realistic cases, this leaves region A strategically weaker under a cap policy than under a tax policy, more so the less carbon-intensive the local fuel (2) is. In conclusion, a fuel-consuming and importing region that determines a climate policy will typically prefer to set a carbon tax, instead of setting a carbon emissions cap. The main reason is that a tax is more efficient than a cap at extracting rent from fuel (oil) exporters.